2009
DOI: 10.1021/jp9035452
|View full text |Cite
|
Sign up to set email alerts
|

Red-Shifted Hydrogen Bonds and Blue-Shifted van der Waals Contact in the Standard Watson−Crick Adenine−Thymine Base Pair

Abstract: Standard Watson-Crick adenine-thymine (AT) base pair has been investigated by using the B3LYP functional with 6-31G(d, p) basis set, at which level of theory the geometrical characteristics of the AT base pair are the best in agreement with the experiment. It exhibits simultaneously red-shifted N-H...O and N-H...N hydrogen bonds as well as a blue-shifted C-H...O contact. AIM analysis suggests that the blue-shifted C-H...O contact exists as van der Waals interaction, and the electron density rho that reflects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 139 publications
5
22
0
Order By: Relevance
“…However, this structure does not address many common RNA secondary and tertiary structural elements. Although the formation of CH⅐⅐⅐O hydrogen bonds in A-T base pairs, both in Watson-Crick and Hoogsteen conformation, has been debated in the literature (37)(38)(39)(40), experiments have yet to definitively resolve whether these interactions represent true hydrogen bonds that stabilize DNA and RNA structure. Corollary studies to those in proteins aimed at directly probing CH⅐⅐⅐O hydrogen bond formation in base pairs, backbone interactions, and tertiary structure represent a promising area of future research.…”
Section: Ch⅐⅐⅐o Hydrogen Bonding In Nucleic Acid Structurementioning
confidence: 99%
“…However, this structure does not address many common RNA secondary and tertiary structural elements. Although the formation of CH⅐⅐⅐O hydrogen bonds in A-T base pairs, both in Watson-Crick and Hoogsteen conformation, has been debated in the literature (37)(38)(39)(40), experiments have yet to definitively resolve whether these interactions represent true hydrogen bonds that stabilize DNA and RNA structure. Corollary studies to those in proteins aimed at directly probing CH⅐⅐⅐O hydrogen bond formation in base pairs, backbone interactions, and tertiary structure represent a promising area of future research.…”
Section: Ch⅐⅐⅐o Hydrogen Bonding In Nucleic Acid Structurementioning
confidence: 99%
“…When the electron density q was about 10 À3 a.u. and its 5 2 q value was smaller than 0.024 a.u., the interaction between two atoms was usually classified as vdW interaction (Zhou & Qiu, 2009). When one of the three eigenvalues was negative and the other two were positive, it was denoted as (3,+1) and was named as the ring critical point (RCP) which indicated the existence of a ring structure.…”
Section: Experimental and Theoretical Investigations Of Five Pigment/mentioning
confidence: 99%
“…Additionally, it was observed that repulsive potential, appearing due to the shortening of intermolecular distances, may be associated with blueshifting patterns. [50][51][52] Neverthe-less, to our knowledge, no first-principles study of the nonelectrostatic vibrational solvatochromism was undertaken up to date. In particular, it is not clear under what circumstances the electrostatic interaction is the dominant contribution 9,42 to experimentally observed vibrational frequency shift.…”
Section: Introductionmentioning
confidence: 99%